1996
DOI: 10.1152/jn.1996.76.6.4140
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of rostral dorsal accessory olive responses during reaching

Abstract: 1. Rostral dorsal accessory olive (rDAO) neurons are sensitive to light touch but have little or no discharge during active movement. We hypothesize that sensitivity of the rDAO is reduced during movement. To test this hypothesis, we evaluated sensitivity of rDAO neurons as cats reached out and retrieved a handle. On selected trials, mechanical or electrical perturbations to the forelimb were presented, and responses of rDAO neurons to the disturbances were recorded. 2. All rDAO units were highly sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 0 publications
6
39
0
Order By: Relevance
“…Because the synchronization task required both perception and motor performance of temporal sequences, the "suppression" of the inferior olive response to the perception component of the task can conceivably be attributed to the concurrent motor activity. This interpretation would be most consistent with electrophysiological studies showing that the responsiveness of the olivary neurons to sensory input is mostly decreased during expected self-produced movement (Gellman et al, 1985;Horn et al, 1996;Apps et al, 1997;Gibson et al, 2002). This may further explain the failure to demonstrate inferior olive activation during timing tasks in previous functional imaging studies that mostly used paradigms requiring motor preparation or motor response (Rao et al, 1997;Schubotz et al, 2000;Ramnani and Passingham, 2001;Dhamala et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Because the synchronization task required both perception and motor performance of temporal sequences, the "suppression" of the inferior olive response to the perception component of the task can conceivably be attributed to the concurrent motor activity. This interpretation would be most consistent with electrophysiological studies showing that the responsiveness of the olivary neurons to sensory input is mostly decreased during expected self-produced movement (Gellman et al, 1985;Horn et al, 1996;Apps et al, 1997;Gibson et al, 2002). This may further explain the failure to demonstrate inferior olive activation during timing tasks in previous functional imaging studies that mostly used paradigms requiring motor preparation or motor response (Rao et al, 1997;Schubotz et al, 2000;Ramnani and Passingham, 2001;Dhamala et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…However, the primary role of the inferior olive and the climbing fiber system in timing and motor control is poorly understood and remains a matter of debate. One view is that the role of the olivo-cerebellar system in timing and error correction of ongoing movement is limited given the relatively slow intrinsic firing rate of the olivary neurons and their variable responsiveness to active movement (Thach, 1968;Armstrong, 1974;Keating and Thach, 1995;Horn et al, 1996;Gibson et al, 2004). However, it has also been suggested that timing of fast movement and modulation of cerebellar output during movement is accomplished by rhythmic and synchronized firing of ensembles of olivary neurons and their population code rather than individual neuronal oscillations (Welsh et al, 1995;Welsh, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report on gating of cutaneous input to climbing fibres terminating within different paravermal cortical zones during the performance of a well-rehearsed reaching task, adding to previous studies concerned with modulation of input to the inferior olive (Horn et al 1996; see also Gellman et al 1985) and modulation of input to climbing fibres during locomotion Apps et al 1990Apps et al , 1995b. Although not without exceptions, response size was usually progressively reduced during the course of the reaching movement, being smallest when the animal was grasping the food with the limb relatively extended.…”
Section: Discussionmentioning
confidence: 69%
“…Cutaneous electrical stimulation (monophasic, square-wave, bipolar, 0.10 ms duration) was used to elicit olivary activity. Evoked olivary activity has variability in timing, polarity, and number of potentials, so the recordings were rectified, integrated (1 ms time constant), digitized (25 kHz sample rate), and averaged across 20 stimulus presentations to provide a reliable estimate of activity (Horn et al, 1996).…”
Section: Methodsmentioning
confidence: 99%